Enteric Coated Sustained Release Mucoadhesive Tablet of Metronidazole for Targeted Colon Delivery: A Formulation and Evaluation Study - Bisht, Latika; Butola, Mansi; Babbar, Assem; Ojha, Abhijeet; Parashar, Tarun; Ale, Yogita; Rana, Shilpa; Jakhmola, Vikash (Indian Journal of Pharmaceutical Education and Research)
Background: Colon-specific Drug Delivery Systems (CDDS) are useful for treating many localized conditions such as ulcerative colitis, Crohn’s disease, irritable bowel syndrome, chronic pancreatitis and colonic cancer. In addition, the colon has the potential to serve as a potential site for the systemic absorption of several drugs used to treat diseases outside of the colon. Drugs, such as proteins and peptides, which are susceptible to degradation under highly acidic gastric conditions, can be absorbed systemically through the colonic mucosa. In order to achieve effective therapeutic outcomes, it is imperative that the designed delivery system specifically targets the drugs in the colon. Objectives: The objective of the current study is to formulate metronidazole sustained-release tablets that can be targeted to the colon because Metronidazole (MNZ) has good solubility at pH 1.2; hence, coating of the drug with the suitable pH dependent is done to prevent its release in the gastric region. Materials and Methods: Metronidazole sustained release tablets were manufactured by using the wet granulation method with hydroxypropyl methylcellulose k100 (HPMC K100), HPMC E-15, Locust bean gum, Sodium alginate and chitosan at different ratios and further coated with suitable polymers. The powdered blend was evaluated for adequate flow properties using Carr’s compressibility index, tapped density, bulk density, angle of repose and Hausner’s ratio before compression. The compressed tablets were then further evaluated for weight variation, hardness, friability, drug content, wash-off test and in vitro dissolution firstly in 0.1 NHCl followed by pH 7.4 phosphate buffer. Results: The friability conducted for every composition is within the appropriate range. The wash-off test F6 composition includes (sodium alginate and HPMC E-15) which shows the best adhesive strength among all the formulations. In the in vitro drug release study, the F6 formulation indicated better controlled delivery i.e., 95.34% in 16 hr. Conclusion: It was found that all of the formulations exhibited a good rate of drug release. Formulation F6 containing sodium alginate and HPMC E-15 exhibited better-controlled release than all other formulations i.e., 95.34% in 16 hr as a result drug release increases with an increase in polymers, exhibiting good mucoadhesive properties. The cumulative drug release percentage for all the formulations was observed to be sustained.
Keywords: Controlled delivery; Enteric-coated; In vitro; Metronidazole; Mucoadhesive.